Intravesical Instillation of Mitomycin C: A Cause of Delayed Bladder Perforation? - Marta Penna; Kiki Mistry; Pallavi Pal; Chitale Sudhanshu (Case Reports in Urology)
We present a case of bladder perforation secondary to intravesical instillation of mitomycin C following transurethral resection of bladder tumour (TURBT) and the role of early detection leading to successful conservative management. We also review the key relevant literature.